Analisis Tajribi terhadap Manfaat Tiktok sebagai Inspirasi Outfit Generasi Z di Kalangan Mahasiswa - Novianda Sukma; Willy Akmansyah Lubis (Prodi Pendidikan Keagamaan Islam, 2023)
This study analyzes the benefits of TikTok as a source of outfit inspiration for Generation Z female students in the Early Childhood Islamic Education Study Program (PIAUD) at STAIN Mandailing Natal. This descriptive qualitative research uses a tajribi approach with data collection techniques including observation, in-depth interviews with 5 fifth-semester students, and documentation, as well as data analysis through reduction, presentation, and verification. The findings indicate that TikTok plays a significant role as a practical, affordable, and aesthetic visual reference for college outfits, enhancing self-confidence and creativity in mix-and-match styles without full imitation. The students selectively adapt the content to Islamic values and campus context, although it may potentially trigger impulsive consumption; the tajribi approach confirms this empirical process as a digital-local dialectic.